2018
DOI: 10.3382/ps/pey057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the minimal available phosphorus needs of laying hens: Implications for phosphorus management strategies

Abstract: The oversupply of dietary phosphorus (P) leads to increased feed costs and discharge of excessive P to the environment, thus directly impacting the sustainability of egg production practices. The present study was conducted to better define the minimal available P needs of laying hens. Fifty-six Lohmann white laying hens were individually caged and fed one of 7 diets with graded levels of available P (0.15, 0.20, 0.25, 0.30, 0.35, 0.40, or 0.45%) for 12 weeks. Records were maintained for body weight, feed inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…In general, plasma P concentration in Sussex hens was lower than that observed in end-of-lay hens by other authors (Dobrzański et al, 2011;Świątkiewicz et al, 2015). However, Jing et al (2018) reported that plasma or serum contain only a small part of total P deposited in the body, which is why changes in plasma P concentration may not necessarily reflect changes in the whole body. This is consistent with our study, because at 64 weeks we found no differences in crude ash or P content of the analysed bones between the breeds.…”
Section: Discussionmentioning
confidence: 71%
“…In general, plasma P concentration in Sussex hens was lower than that observed in end-of-lay hens by other authors (Dobrzański et al, 2011;Świątkiewicz et al, 2015). However, Jing et al (2018) reported that plasma or serum contain only a small part of total P deposited in the body, which is why changes in plasma P concentration may not necessarily reflect changes in the whole body. This is consistent with our study, because at 64 weeks we found no differences in crude ash or P content of the analysed bones between the breeds.…”
Section: Discussionmentioning
confidence: 71%
“…The frozen tibiae were thawed at room temperature for 2 h and then stripped of all soft tissues. The tibia BMD ( Liu et al., 2017 , Jing et al., 2018 ) was determined by dual-energy X-ray absorptiometry. The tibia BBS was determined by a 3-point bending test (HDP/3PB Texture Analyzers, West Sussex, UK).…”
Section: Methodsmentioning
confidence: 99%
“…A scan of the whole bone was performed using the "small animal" mode of the enCORE ® software (version 17.0 (2016); GE, Madison, WI, USA) and a special pad for "small animal" scans provided by the producer densitometer, which was used to eliminate measurement artifacts and to immobilize the bones so that all the bones were scanned in the coronal plane. No additional objects were used to mimic the soft tissue around bone [17,18,44]. The measurements were carried out on the scanned data using operator-defined regions of interest (ROIs) covering the central, 40 mm long fragment of the tibial bone, at the mid-diaphysis.…”
Section: Bone Measurements and Bone Sample Preparationmentioning
confidence: 99%